2011
DOI: 10.19030/ctms.v1i3.5237
|View full text |Cite
|
Sign up to set email alerts
|

Successfully Teaching Ethics For Effective Learning

Abstract: This paper is concerned with identifying keys to successfully teach ethics. The keys are: addressing the relevance challenge; striving to achieve a balance between the active engagement of students with issues and a critical analysis of choices in to be made in real-life situations; attending to or managing the learning process to include learning styles and experiential learning; debriefing experientially-oriented learning activities; and institutionalizing outcomes of ethics education objectives. The paper d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…These learning domains will affect students' experience deeper and memorable [15]. Sims (2002) also agree the learning process can leave a memorable impression to constructivists [16]. This research focus on simulation software named Cisco Packet Tracer that provides students to have an active learning experience and bring the real networking environment into the classroom.…”
Section: Learning Theoriesmentioning
confidence: 99%
“…These learning domains will affect students' experience deeper and memorable [15]. Sims (2002) also agree the learning process can leave a memorable impression to constructivists [16]. This research focus on simulation software named Cisco Packet Tracer that provides students to have an active learning experience and bring the real networking environment into the classroom.…”
Section: Learning Theoriesmentioning
confidence: 99%
“…Quite often students believe that there are only two options, when in fact only through class discussion and an application of moral imagination (Werhane, 1999) do additional and more ethically appropriate alternatives arise. Role-playing, whereby students act out various roles as described in the ethical dilemma, can also be used as a teaching technique (Sims, 2002). Role-playing can further engage the students and lead to prescripting behavior, which can increase the likelihood of actually engaging in ethical behavior in the future (Gentile, 2010).…”
Section: Pedagogical Tools For Teaching Behavioral Ethicsmentioning
confidence: 99%
“…Still, others are neutral and adopt a Bthere is no harm in tryingd isposition, and others are positive about its benefits and support it (McDonald and Donleavy 1995). Sims (2002) found that the first step in instituting a policy was for the faculty to declare that it believes in the importance of ethics education. Also, if policy makers do not believe in the relevance and effectiveness of incorporating ethics content into the curriculum, they will not be willing to commit time and resources to see it through (Uyar and Gungormus 2013).…”
Section: Factors Affecting Ethics Educationmentioning
confidence: 99%